Ethical leadership concerning the establishment and promotion of sustainable tourism in the hospitality industry: A review of literature and qualitative analysis - Fowler, David S.; Cheraghi, Faezeh; Valverde, Bryahana (Hotel and Tourism Management, 2022)
This research study is a succinct review of the literature concerning ethical leadership in the hospitality industry and challenges with the establishment and promotion of sustainable tourism. The study takes a qualitative analysis approach to discover congruent themes concerning ethical leadership?s establishment and promotion of sustainable tourism. The aim of the research is to provide a launching point for additional inquiry as it is foundational in purpose to illicit further examination.